19th International Conference on Ultrafast Phenomena 2014
DOI: 10.1364/up.2014.10.thu.e.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Regime of Nanoscale Thermal Transport: Collective Diffusion Counteracts Dissipation Inefficiency

Abstract: Understanding thermal transport from nanoscale heat sources is important for a fundamental description of energy flow in materials, as well as for many technological applications including thermal management in nanoelectronics, thermoelectric devices, nano-enhanced photovoltaics and nanoparticle-mediated thermal therapies. Thermal transport at the nanoscale is fundamentally different from that at the macroscale and is determined by the distribution of carrier mean free paths in a material, the length scales of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…HHG enables tabletop generation of coherent beams of extreme ultraviolet (EUV) and soft x-ray light [4], which have a broad range of applications. For example, HHG makes it possible to capture chemical reactions in real time [5][6][7], to uncover correlated charge/spin/phonon dynamics in materials with elemental specificity [8][9][10], and to perform coherent imaging on the nanometer scale near the wavelength limit [11,12]. Similarly, recent studies have revealed that the photoelectron distribution from SFI can provide information about dynamic orbital and molecular structure [13][14][15][16], indicating its potential for understanding molecular dynamics.…”
mentioning
confidence: 99%
“…HHG enables tabletop generation of coherent beams of extreme ultraviolet (EUV) and soft x-ray light [4], which have a broad range of applications. For example, HHG makes it possible to capture chemical reactions in real time [5][6][7], to uncover correlated charge/spin/phonon dynamics in materials with elemental specificity [8][9][10], and to perform coherent imaging on the nanometer scale near the wavelength limit [11,12]. Similarly, recent studies have revealed that the photoelectron distribution from SFI can provide information about dynamic orbital and molecular structure [13][14][15][16], indicating its potential for understanding molecular dynamics.…”
mentioning
confidence: 99%